Some experiments concerning fish processing into minced products aboard the Romanian trawlers - Pintilie, Angela (Cercetări Marine - Recherches Marines, 2026)
The paper presents the results of some experiments made aboard Romanian fishing vessels concerning minced fish meat processing. It was used small-sized fish which is industrial caught between Mars-June 1978 at the west African shore.